Frequency Dependence Hearing Loss Evaluation in Perforated Tympanic Membrane - Dawood,Mohammed Radef (2017)
Abstract Introduction Tympanic membrane perforation is a relatively common problem that predisposes patients to varying degrees of conductive hearing loss. Objective The objective of this study is to evaluate and analyze the frequency dependence hearing loss in tympanic membrane perforation based on the size and the site of perforation. Methods For the study, I selected 71 patients’ (89) ears for the cross-sectional study with tympanic membrane perforations; I examined the size and the site of perforations under the microscope and classified them into small, moderate, large, and subtotal perforations, and into anterior central, posterior central, malleolor central, and big central perforations. I measured mean level of speech frequencies hearing loss, and its relation with the site and the size of the perforation analyzed. Results The mean hearing loss at different sizes of the perforation at all speech frequencies was 37.4 dB, with ABG of 26.6 dB, and its maximum loss was detected in subtotal perforation of 42.3 dB, with ABG of 33.7 dB, at 500 Hz frequency, while in relation to the sites, it was 38.2 dB, with ABG of 26.8 dB, and its maximum loss was detected in big central site perforation of 42.1 dB, with ABG of 33.6 dB, at 500 Hz frequency. Conclusions The hearing loss was proportionally related with the sizes of the perforations, and the posterior site had greater impact on the hearing than anterior site perforations. This was also applied to the frequency dependence hearing level, as was detected to be worse at lower frequencies as 500 Hz, than those of 1000-2000 Hz.